Savoirs locaux et agriculture durable au Yémen Séminaire 'Place des pratiques et techniques anciennes dans l'agriculture yéménite d'aujourd'hui : problèmes et perspectives', Sanaa, juin 2000 - Pelat, Frédéric; Al-Hakimi, Amin (Histoire et société de la péninsule Arabique, 2003)
This third publication of 'Cahiers du CEFAS' -previously named 'Cahiers du CFEY'- results from a partnership with the Yemeni Genetic Resources Center (YGRC) and consists of 19 articles selected from the seminar The place of ancient agricultural practices and techniques in Yemen today : problems and perspectives, held in June 2000, at the Faculty of Agriculture of Sanaa University and in the CEFAS. More than 30 anthropologists, archaeologists, geographers, historians, agronomists and development specialists, from Yemen and abroad, participated in the meetings. Far from being a nostalgic point of view on a potentially 'unchanging' Yemeni agriculture, protected from any 'harmful' modernisation of its practices and techniques, and at the same time, far from discrediting 'excessive' technological improvements and their effects on environment or food quality, this seminar was clearly dedicated to sharing ideas related to development operations in this mainly rural country, where any development policy has to, in all cases, rely upon farmers' labour.